Location of mental foramen in a southeast iranian population: a digital panoramic assessment - Eshagh ali Saberi; Reza Kazemian; Narges Farhadmollashahi; Abbas Mohammadi; Farnaz Alidadiani (Babol University of Medical Sciences, 2017)
Introduction: Mental foramen is an important landmark in mandible and knowledge regarding the actual location of mental foramen is important in dentistry. Materials &Methods: A total of 1172 digital panoramic radiographs were evaluated for assessment of the location of the mental foramen. The location was classified into six groups in relation to the apices of the premolars and first molar. Results: In 957 of panoramic radiographs, fulfilling the inclusion criteria, the most common location of the mental foramen was at the apex of the mandibular second premolar. In 837 cases (87.5%), the mental foramen was located symmetrically on both sides of the mandible. Therefore, the apex of the second premolar was the most common symmetric location in both genders. Conclusion: The results showed that the most common location of the mental foramen in population of southeast Iran was at the apex of the second premolar.